Modern military geography - Galgano, Francis A.; Palka, Eugene J. (Routledge, 2011)
This book of contributed chapters by subject matter expertly provides an overview and analysis of salient contemporary and historical military subjects from the military geographer's perspective. Factors of geography have had a compelling influence on battles and campaigns throughout history; however, geography and military affairs have gained heightened attention during the past two decades, and military geography is the discipline best situated to explain them. Hence, the premise of this book and its contents are founded on the principle that geographical knowledge of space, place, people, and scale provide essential insights into contemporary security issues and promotes the idea that such insight is critical to understanding and managing significant military problems at local, regional, and global scales.